The Acculturation of Local and Islamic Culture in the Pattorani Tradition on Masalima Island, Pangkep Regency - Hayati, Amirullah; Yunus, Abd. Rahim; Santalia, Indo (Pascasarjana UIN Alauddin Makassar, 2023)
The main problem in this study is the acculturation of local and Islamic culture in the pattorani tradition on Masalima Island, Pangkep Regency. The type of research used was cultural research using descriptive research methods. The approach used is a historical approach with a theological approach. The data sources for this study were primary and secondary data, using research data collection methods such as observation, interviews, and documentation. Then, data processing and analysis techniques were conducted in three method stages: Inductive, deductive, and comparative. The results of this study showed that the origins of the pattorani tradition on Masalima Island, Pangkep Regency, were carried out before the arrival of Islamic teachings based on mythical community beliefs. The two series of pattorani traditions such as; first, it took place at the puggawa's house; then it continued on the beach edge and then on a boat with several rituals, namely: parenta pakkaja, appassili biseang, and accaru-caru beseang. Then, the fishermen's wives had a banquet near the bridge, and pamacca was also held. After the Pattorani season, the community held a second banquet while listening to religious discourse and sending Salawat. Third, the pattorani tradition has a form of acculturation of local and Islamic culture, such as prayer, barazanji, religious discourse, and sending salawat, which has Islamic values such as spiritual and cooperation values.